Conceptualizing intubation sharing: A descriptive qualitative study of videolaryngoscopy for pediatric emergency airway management. Issue 2 (4th April 2021) - Miller, Kelsey A; Marchese, Ashley; Luff, Donna; Nagler, Joshua
Abstract: Background: This study characterizes clinical and educational practices around the use of videolaryngoscopy in pediatric emergency airway management through qualitative exploration. Methods: This is a descriptive qualitative study using semi‐structured interviews of emergency medicine physicians. Physicians were selected by theoretical sampling from urban, tertiary care pediatric hospitals across the United States until theoretical data saturation was achieved. The study applied a constructivist grounded theory approach to data collection and analysis. Manual line‐by‐line coding of interview transcripts was used initially, then grouped into categories with constant comparative analysis to generate the final coding scheme organized by themes and subthemes. Finally, memo‐writing and iterative analysis meetings explored relationships between themes and identified an interpretive model. Results: Theoretical saturation was achieved after 10 of the initial 12 interviews. Emerging from the data were six themes that describe the concept of intubation sharing: (1) Videolaryngoscopy encompasses multiple modalities that all provide a shared view and ability to record; (2) Airway experts and systems help realize the full potential of videolaryngoscopy; (3) Videolaryngoscopy can be a clinical, educational, quality assurance and research tool; (4) Some skills required for videolaryngoscopy are unique, while others overlap with direct laryngoscopy; (5) Videolaryngoscopy allows a coaching laryngoscopist to provide real‐time guidance to the primary laryngoscopist from a shared view; (6) Videolaryngoscopy provides an opportunity for post‐intubation coaching and feedback and shared learning from a single experience for the provider community. Conclusions: Through this multicenter qualitative interview study, we derived the concept of intubation sharing through videolaryngoscopy for real‐time and remote coaching, for both the primary laryngoscopist and the community of emergency medicine providers who intubate.